The Irish Programme to Eradicate Bovine Viral Diarrhoea Virus—Organization, Challenges, and Progress - Graham, David; More, Simon J.; O'Sullivan, Padraig; Lane, Elizabeth; Barrett, Damien; Lozano, Jose-Maria; Thulke, Hans-Hermann; Verner, Sharon; Guelbenzu, Maria (Frontiers in Veterinary Science, 2021)
A mandatory national Irish bovine viral diarrhoea (BVD) eradication programme, coordinated by Animal Health Ireland, commenced in 2013. Key decisions and programme review are undertaken by a cross-industry Implementation Group (BVDIG) supported by a Technical Working Group. Ear notch tissue is collected from all new-born calves using modified official identity tags, supplemented by additional blood sampling, including for confirmatory testing of calves with initial positive results and testing of their dams. Testing is delivered by private laboratories in conjunction with the National Reference Laboratory, with all results reported to a central database. This database manages key elements of the programme, issuing results to herdowners by short message service messaging supplemented by letters; assigning and exchanging animal-level statuses with government databases of the Department of Agriculture, Food and the Marine to enable legislated restrictions on animal movements; assigning negative herd status based on test results; generating regular reports for programme management and evaluation and providing herd-specific dashboards for a range of users. Legislation supporting the programme has been in place throughout but has not thus far mandated the slaughter of persistently infected (PI) calves. A key challenge in the early years, highlighted by modeling, was the retention of PI animals by some herd owners. This has largely been resolved by measures including graduated financial supports to encourage their early removal, herd-level movement restrictions, ongoing programme communications and the input of private veterinary practitioners (PVPs). A framework for funded investigations by PVPs in positive herds was developed to identify plausible sources of infection, to resolve the status of all animals in the herd and to agree up to three measures to prevent re-introduction of the virus. The prevalence of PI calves in 2013 was 0.66%, within 11.3% of herds, reducing in each subsequent year, to 0.03 and 0.55%, respectively, at the end of 2020. Recent regulatory changes within the European Union for the first time make provision for official approval of national eradication programmes, or recognition of BVD freedom, and planning is underway to seek approval and, in due course, recognition of freedom within this framework by 2023.